The influence of aortoseptal angulation on provocable left ventricular outflow tract obstruction in hypertrophic cardiomyopathy. Issue 1 (30th October 2014) - Critoph, Christopher Howell; Pantazis, Antonios; Tome Esteban, Maria Teresa; Salazar-Mendiguchía, Joel; Pagourelias, Efstathios D; Moon, James C; Elliott, Perry Mark
Abstract : Objectives: Aortoseptal angulation (AoSA) can predict provocable left ventricular outflow tract obstruction (LVOTO) in patients with symptomatic hypertrophic cardiomyopathy (HCM). Lack of a standardised measurement technique in HCM without the need for complex three-dimensional (3D) imaging limits its usefulness in routine clinical practice. This study aimed to validate a simple measurement of AoSA using 2D echocardiography and cardiac MR (CMR) imaging as a predictor of LVOTO. Methods: We retrospectively assessed 160 patients with non-obstructive HCM, referred for exercise stress echocardiography. AoSA was measured using resting 2D echocardiography in all patients, and CMR in 29. Twenty-five controls with normal echocardiograms were used for comparison. Results: Patients with HCM had a reduced AoSA compared with controls (113°±12 vs 126°±6), p<0.0001. Sixty (38%) patients had provocable LVOTO, with smaller angles than non-obstructive patients (108°±12 vs 116°±12, p<0.0001). AoSA, degree of mitral valvular regurgitation and incomplete systolic anterior motion (SAM) were associated with peak left ventricular outflow tract gradient (r=0.508, p<0.0001). An angle ≤100° had 27% sensitivity, 91% specificity and 59% positive predictive value for predicting provocable LVOTO. When combined with SAM, specificity was 99% and positive predictive value 88%. Intraclass correlation coefficient of AoSA measured by two observers was 0.901 (p<0.0001). Bland-Altman analysis of echocardiographic AoSA showed good agreement with the CMR-derived angle. Conclusions: Measurement of AoSA using echocardiography in HCM is easy, reproducible and comparable to CMR. Patients with provocable LVOTO have reduced angles compared with non-obstructive patients. AoSA is highly specific for provocable LVOTO and should prompt further evaluation in symptomatic patients without resting obstruction.